Optimization of multilayer antireflection coating for solar cells: article / Norhuda Hamzah - Hamzah, Norhuda (2009)
This paper presents the effects of Silicon dioxide (Si02> and Silicon nitride (SiN) used as an antireflection (AR) coating for solar cell. The ATLAS simulator of Silvaco TCAD tools was used to simulate the photovoltaic cells. Basically, this paper describes the simulation of highest conversion efficiency for solar cell with double layer Si02-SiN antireflection coating. The same parameter will be investigated for triple AR coating as well. For photovoltaic applications, the refractive index, and thickness are chosen in order to minimize the reflection. In this project, the refractive index used is 1.46 for Si02 and 2.05 for SiN and the thickness of SiN is fixed as 0.05um and varies the Si02. When thickness of Si02 is 0.09um, the external quantum efficiency measurements showed that the double layer Si02-SiN is more efficient than three layers Si02-SiN-SiN with 97.8% efficiency.